Analisis Karakteristik Briket Berbahan Kulit Buah Lontar dan Batang Bambu Sebagai Bahan Bakar Alternatif - Rahmatul iman, Novan; Aldrin, Aldrin; Dzil Ikram, Fadhli; Hidayat, Amri (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2025)
When renewable fuel energy is running out, many academics and practitioners are starting to try to make alternative fuels that come from renewable resources. To reduce our dependence on fossil fuels, this is very important to do, one of the renewable energies that has great potential in Indonesia in biomass. Biomass energy includes livestock, plantations, wood, and industrial and household organic materials. The aim of this research is to determine the characteristics of briquettes mixed with palm fruit and bamboo sticks. The best composition of a mixture of palm fruit and bamboo stems in this research was in sample 5 a mixture of 25% palm fruit : 65% bamboo stem with 10% adhesive had a water content of 11.17%, ash content of 57.59%, volatile matter content of 19.62%, bound carbon content 48.73% and heating value 4.288 cal/g.